Clinical significance of metabolism-related biomarkers in non-Hodgkin lymphoma-MCT1 as potential target in diffuse large B cell lymphoma - Afonso, Julieta (2019)
PurposeIncreased glycolytic activity with accumulation of extracellular lactate is regarded as a hallmark of cancer. In lymphomas, FDG-PET has undeniable diagnostic and prognostic value, corroborating that these tumours are avid for glucose. However, the role of glycolytic metabolism-related molecules in lymphoma is not well known. Here, we aimed to evaluate the clinical and prognostic significance of a panel of glycolytic metabolism-related molecules in primary non-Hodgkin lymphomas (NHL) and to test in vitro the putative therapeutic impact of lactate transport inhibition.MethodsWe assessed, by immunohistochemistry, the expression of the metabolism-related molecules MCT1, MCT2, MCT4, CD147, GLUT1, LDHA and CAIX in both tumour and stroma compartments of tissue sections obtained from 104 NHL patients. In addition, the lymphoma-derived cell lines OZ and DOHH-2 were used to evaluate the effect of AZD3965 on their viability and on apoptosis induction, as well as on extracellular lactate accumulation.ResultsWe found that expression of MCT1 in the NHL tumour compartment was significantly associated with a poor clinicopathological profile. We also found that MCT4 and CAIX were present in the stromal compartment and correlated with an aggressive phenotype, while MCT1 was absent in this compartment. In addition, we found that AZD3965-mediated disruption of MCT1 activity led to inhibited NHL cell viability and extracellular lactate accumulation, while increasing apoptotic cell death.ConclusionsOur results indicate that elevated glycolytic activity is associated with NHL aggressiveness, pointing at metabolic cooperation, mediated by MCT1 and MCT4, between tumour cells and their surrounding stroma. MCT1 may serve as a target to treat NHL (diffuse large B cell lymphoma) patients with high MCT1/low MCT4 expressing tumours. Further (pre-)clinical studies are required to allow the design of novel therapeutic strategies aimed at e.g. reprogramming the tumour microenvironment.